Pemanfaatan Tumbuhan Alang-Alang (Imperata Cylindrica L) sebagai Obat Tradisional oleh Masyarakat Desa Selasi Kabupaten Buru Selatan - Loilatu, Bihima; Rumra, M. Yamin; Subhan, Subhan (HORIZON: Indonesian Journal of Multidisciplinary, 2023)
The purpose of this study was to determine the use of alang-alang plants as traditional medicine by the people of Selasi Village, South Buru Regency. The type of research used in this study is qualitative descriptive with 5 subjects. The instruments used in this study were observation and interviews. Observation is used to observe the process of using reed plants as traditional medicine and interviews are used to find out how to process reed plants. The data analysis techniques used follow qualitative data analysis with stages of data reduction, data presentation, and conclusion drawing. The results of data analysis are known that the use of alang-alang plants as traditional medicine has long been used by the people of Selasih Village. The process of processing plants is carried out traditionally by the community and is carried out based on knowledge possessed from generation to generation inherited by people before them. In general, reed plants can be used as internal medicine or external medicine. As a medicine in including can cure stomach disease, ulcers, vomiting blood, and kidney drugs. While as an external medicine, reed plants can be used as wound medicine due to falling or because of cuts